Indeks Patriotisme : Kepentingan dan Sumbangan Mahasiswa Kepada Negara - Mohammad Shatar Sabran, author 405397; Ahmad Ariffian Bujang, author 382438; Abd. Jamal Ibrahim, author 405071; Ahmad Esa, 1965-, author; Ahmad Tajuddin Othman, author 364360; Amini Amir Abdullah, author 256152; Azali Rahmat, author 606305; Azlan Abdul Latib, 1970-, author 509773; Faudziah Shukor, 1957-, author 404935; Johar Md. Lajis, author 606298; Juhari Ab. Razak, author 226262; Mansor Ahmad Saman, author 187002; et al. (Putrajaya : Jabatan Pendidikan Tinggi, 2016)
Includes bibliographical references.